Music as a site for Africanness and diaspora cultures: African musicians in the white landscape of Finland. Issue 1 (2nd January 2016) - Rastas, Anna; Seye, Elina
ABSTRACT: This article looks at African musicians in Finland and the ways that they negotiate ideas of 'Africanness' in their professional activities. The specific environment of Finland with a relatively low number of people of African descent inevitably shapes the activities of these musicians. Our analysis, based on our many years of fieldwork among African diaspora communities, makes visible the multiplicity of sites where African music is played and performed in Finland, and the various contexts that influence the ways in which Africanness is articulated. In a predominantly white society, African musicians' roles extend from artists and 'cultural ambassadors' to active change agents in the fields of identity politics and anti-racism struggles.